A review on the electrical properties of doped SrTiO3 as anode materials for solid oxide fuel cells. (20th September 2019) - Li, Runping; Zhang, Cheng; Liu, Jianhua; Zhou, Junwen; Xu, Lei
Abstract: To obtain a solid oxide fuel cell anode material with good performance, the researchers improved the conductivity and catalytic activity of the material by doping pure SrTiO3 . In this paper, the research progress of A-doped, B-doped and (A, B)-co-doped SrTiO3 anode materials was reviewed. The effects of doping on the SrTiO3 anode material were analyzed for different doping types, elements and concentration, atmospheric conditions, temperature and defect type. The common doping elements in the A site were La and Y, and the total conductivity of the material was improved by A-site doping. The common doping elements in the B site were Fe and Nb which improved the ionic and total conductivities of the material via B-site doping, respectively. The (A, B)-co-doped SrTiO3 material had high catalytic activity, good stability, proper porosity and superior chemical compatibility and thermal expansion with solid electrolytes. The (A, B)-co-doped SrTiO3 material also had strong mixed electronic-ionic conductivity which improved the electrical properties of the material.